2017
DOI: 10.1155/2017/2062157
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Complete Anal Stricture after Diverting Colostomy for Fournier’s Gangrene

Abstract: Background. Anal stenosis is a rare but serious complication of anorectal surgery. Severe anal stenosis is a challenging condition. Case Presentation. A 70-year-old Japanese man presented with a ten-hour history of continuous anal pain due to incarcerated hemorrhoids. He had a history of reducible internal hemorrhoids and was followed for 10 years. He had a fever and nonreducible internal hemorrhoids surrounding necrotic soft tissues. He was diagnosed as Fournier's gangrene and treated with debridement and div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Apart from the study by Gülen et al [ 26 ], the terms ‘rhomboid’ and ‘diamond’ referred to an identical flap shape [ 2 , 13 , 14 , 15 , 23 , 27 ]. While several studies reported the outcomes of the house flap for AS [ 2 , 16 , 18 , 32 , 34 , 35 ], a smaller number described those of a rectal advancement flap [ 7 , 25 , 31 ], anal advancement flap [ 4 ], V–Y flap [ 7 , 36 ] or C‐plasty [ 20 ]. Eight studies reported early experience with more technically demanding operations, but these were limited to one to three cases [ 4 , 14 , 21 , 22 , 24 , 29 , 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Apart from the study by Gülen et al [ 26 ], the terms ‘rhomboid’ and ‘diamond’ referred to an identical flap shape [ 2 , 13 , 14 , 15 , 23 , 27 ]. While several studies reported the outcomes of the house flap for AS [ 2 , 16 , 18 , 32 , 34 , 35 ], a smaller number described those of a rectal advancement flap [ 7 , 25 , 31 ], anal advancement flap [ 4 ], V–Y flap [ 7 , 36 ] or C‐plasty [ 20 ]. Eight studies reported early experience with more technically demanding operations, but these were limited to one to three cases [ 4 , 14 , 21 , 22 , 24 , 29 , 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Okumura K et al, have reported the only other case report of complete anal stenosis following Fournier's gangrene debridement [5].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the anorectal region, this infection occurs when hemorrhoidal fistulae are present. [4] Treatment may involve Thiersch operation for rectal prolapse, [5] hemorrhoid treatment, [6][7][8][9] or chemotherapy or chemoradiotherapy for patients with rectal cancer. [10,11] Fournier's gangrene is frequently accompanied by an underlying systemic disease, diabetes mellitus, and heavy alcohol consumption [12,13] ; other causes include leukemia [14,15] and the human immunodeficiency virus.…”
Section: Introductionmentioning
confidence: 99%